2022
DOI: 10.3389/fendo.2022.947586
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes of retinal microvascular circulation and RNFL thickness measured by optical coherence tomography angiography in patients with obstructive sleep apnea–hypopnea

Abstract: PurposeTo evaluate capillaries perfusion and retinal nerve fiber layer (RNFL) thickness diurnal changes of macular/optic disc regions among participants with or without obstructive sleep apnea-hypopnea (OSA) using spectral-domain optical coherence tomography angiography (OCTA).MethodsIn this study, we enrolled a cohort of 35 participants including 14 patients with mild-to-moderate OSA, 12 patients with severe OSA, and 9 healthy individuals. All participants had Berlin questionnaire filled. At 20:00 and 6:30, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…We also concluded that the pooled RPC whole enface VD was substantially lower in the severe OSAS group compared with the control group ( P =0.001, Figure 3 ). Our current data strongly consolidated the results of prior studies [ 22 , 24 ]. Besides, no obvious heterogeneity was found in our meta-analysis (chi 2 = 3.35, I 2 = 10%; chi 2 = 1.24, I 2 = 0%, respectively), as described in Figures 2 and 3 .…”
Section: Discussionsupporting
confidence: 90%
“…We also concluded that the pooled RPC whole enface VD was substantially lower in the severe OSAS group compared with the control group ( P =0.001, Figure 3 ). Our current data strongly consolidated the results of prior studies [ 22 , 24 ]. Besides, no obvious heterogeneity was found in our meta-analysis (chi 2 = 3.35, I 2 = 10%; chi 2 = 1.24, I 2 = 0%, respectively), as described in Figures 2 and 3 .…”
Section: Discussionsupporting
confidence: 90%
“…The foveal region was defined as the area within a central circle with a 1 mm diameter; the parafoveal area was an annulus around the fovea with 1 and 3 mm inner and outer ring diameters, respectively; and the perifovea represented the region of the outer annulus beyond the parafovea with a 6-mm diameter. The VD of the choriocapillaris was calculated as the ratio of the flow area within a circle of radius 1 mm around the fovea [ 21 , 22 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%